Constraint As an Ethical Postulate in the Context of Ecological Limits - Stachowska, Iwona (ETHICS IN PROGRESS, 2016)
The problem of natural resources being finite as well as the capability of ecosystems and the biosphere to assimilate the effects of economic activity on the one hand, and growing economic discrepancies on the other raise a question mark over the chase after the unrestrained economic growth. In the search for alternative models of thinking and development a significant role of constraint is being more and more emphasized. In the case of ecological barriers limitation of using non-renewable resources, greenhouse gases emissions, excessive consumption and production seems to be a reasonable strategy that manifests our care for the natural environment. The aim of the paper is to demonstrate that the postulate of constraint present in the de-growth model in the form proposed by Tim Jackson and Serge Latouche apart from a quantitative dimension has, above all, a qualitative and ethically orientated dimension. Constraint conceived in the above way stays close to terms like moderation, restraint, sustainability, i.e. such terms that possess solid ethical foundations and constitute an important base for environmental ethics.